A Study on the relationship between the teaching skills and delivery of contents in teaching of primary schools in Nepal - Pokhrel, Bhumi Shwor (KDI School, 2011)
“The Nepali education system does provide some pre-service and in-service teaching skills training for teachers in primary and secondary levels. At the moment, the teaching skills training program has benefited about half of those in the teaching profession. It remains doubtful; however, how many of the trained teachers are putting to practical use the teachings skills they have learned. This thesis is an empirical study to document the relationship between teaching skills training and their actual usage in the classroom delivery of contents, and identify factors that facilitate the actual use of teaching skills in the classroom setting. Since limited number of research studies related to delivery of training skills were conducted in the past, this particular area i.e. delivery of content was taken into consideration for the present study. Two types of respondents were selected ? the head teachers and teachers of primary and non-primary schools. Four types of survey instruments such as school survey forms, class observation form, teacher interview form and head teacher interview form were prepared and used to carry out the study. The class observation forms were filled up on the basis of class observation of teachers by researcher himself. Rest of the three tools was administered by interviewing the teachers and head teachers. During the study, it was assumed that there was a strong relationship between teaching skills and delivery of contents. Some teaching skills were found to have been used in the schools where there were some positive attributing factors to facilitate teaching skills. However most of the teaching skills received by teachers in the training were not found to have used due to personal ignorance of teachers and head teachers, worse physical facilities and poor economic condition of schools. If quality training is provided to the teachers by training centers, teachers’ jobs are appraised regularly, authorities are delegated to the head teachers sufficiently and schools are physically dependable, then there is a full hope of utilization of teaching skills. Otherwise government’s economic inputs to training sectors will not bring desirable results.’’
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Nepal.